(untitled) (Altre Modernità, 2018)
Sibyl is a mythological figure that provides an opportunity to reflect on the conscious comparativism in the past. Through the ananlysis of four texts (Paus., Per., I, 2,2; Or. Sib., III, vv. 813-823; Erma, Vis., I e II; Mundus Origo, vv. 1-6), in which the Sibyl is described as a prototype of the classical, jewish and christian prophetic imaginary, we discuss among the possibility of a comparative attitude of authors from the Classical Age to the Late Antiquity. The tipology of Sibyl’s descriptions can explain the role of this seer in order to define an <identity island>. This approach demonstrates how different and distant populations elaborated a mythological boundary, a frontier where an evolutive, historical and genetic contact was possible, according to the method founded by A. Gnisci and M. Detienne, in collaboration with the psycological-mythological parameter. As a metamorphic clone, the Sibyl provides a consideration on the usefulness of contents offered by a silent comparativism of the past. It gives a new perspective to the modern-contemporaneus comparativism, evaluating the necessity of a dialogue between literatures and cultures in a synchronic and diachronic sense.